How does a social norms-based intervention affect behaviour change? Interim findings from a cluster randomised controlled trial in Odisha, India - Hagere Yilma; Erica Sedlander; Satyanarayan Mohanty; Ichhya Pant; Jeffrey Bingenheimer; Lipika Patro; Rohini Ganjoo; Rajiv Rimal (BMJ Open)
Background Behaviour change interventions targeting social norms are burgeoning, but researchers have little guidance on what they look like, and which components affect behaviour change. The Reduction in Anaemia through Normative Innovations (RANI) project designed an intervention to increase iron folic acid (IFA) consumption in Odisha, India.Objective This paper examines the effect of the intervention at midline to understand which components of the RANI intervention affect uptake.Methods Using a cluster randomised controlled design, we collected baseline data and midline data 6 months later from women of reproductive age in the control and treatment arms (n=3800) in Angul, Odisha, India. Using nested models, we analysed data from three different intervention components, monthly community-based testing for anaemia, participatory group education sessions, and videos, to determine the extent to which exposure to each of these components accounted for the overall intervention effect on haemoglobin and self-reported IFA use.Results Overall, residing in a treatment as opposed to control village had little effect on midline haemoglobin, but increased the odds of taking supplements by 17 times. Exposure to each of the intervention components had a dose–response relationship with self-reported IFA use. These components, separately and together, accounted for most of the overall effect of treatment assignment on IFA use.Conclusions All intervention components increased iron supplement use to differing degrees of magnitude. It appears that a social norms-based approach can result in improving IFA uptake, though improvements in haemoglobin counts were not yet discernible.